The New Analysis for the Caputo-Fabrizio Fractional Gas Dynamics Model with the Robust Technique - Alkan, Aslı (Erzincan Binali Yıldırım Üniversitesi, 2026)
The Caputo-Fabrizio fractional gas dynamics equation is analyzed using the robust method. Numerical solution of this equation are represented in 2D and 3D graphs using Maple software. Table 1 demonstrates the effectiveness and consistency of the proposed method. The ?-curves of the obtained solutions are plotted. The derived solutions facilitated a physical understanding of the gas dynamics equation.

Caputo-Fabrizio kesirli mertebeden gaz dinamiği denklemi, güçlü yöntem kullanılarak analiz edilmiştir. Bu denklemin sayısal çözümü Maple yazılımı kullanılarak 2D ve 3D grafiklerle gösterilmiştir. Tablo 1 önerilen yöntemin etkinliğini ve tutarlılığını göstermektedir. Elde edilen çözümlerin ? eğrileri çizilmiştir. Türetilen çözümler gaz dinamiği denkleminin fiziksel olarak anlaşılmasını kolaylaştırmıştır.
Caputo-Fabrizio Kesirli Gaz Dinamiği Modeli için Güçlü Yöntemle Yeni Sayısal Analiz
Keywords: Applied Mathematics (Other); Uygulamalı Matematik (Diğer)